Business Analysis of Illegal Selling and Copyrights Violation on E-Commerce (Case Study Shopee) - I Putu Hendika Permana (Catuspata, 2021)
Nowadays technology is growing rapidly. Buying and selling interactions that are usually done directly can now be done online through E-Commerce applications. Because more and more people are using E-Commerce applications, the government makes regulations regarding the PMSE Government Regulation which was set in 2019. This article was carried out with the aim of finding out whether there are still business actors who do not follow the PMSE Government Regulation. This research focuses more on business actors who sell book products and also software applications on the Shopee application. This research uses three methods, namely conducting a literature study related to the PMSE Government Regulation, exploring the E-Commerce platform, conducting interviews with buyers or book readers and book creators. This study shows the results that there are still business actors who do not follow the PMSE Government Regulations. The implication of finding business actors on E-Commerce Shopee who do not follow PMSE Government Regulations is that in future research they can conduct research on other E-Commerce platforms, for example such as Lazada, Tokopedia, JD ID and other platforms.